Primary Extranodal Follicular Lymphoma: A Retrospective Survey of the International Extranodal Lymphoma Study Group (IELSG) - Conconi, Annarita; Janikova, Andrea; Vannata, Barbara; Ramírez-Ibarguen, Ana Florencia; Lobetti-Bodoni, Chiara; Belada, David; Pirosa, Maria Cristina; Mian, Michael; Ferreri, Andrés J M; Ryan, Gail; Pangalis, Gerassimos; Cabrera, Maria Elena; et al. (Hematological oncology, 2025)
The characteristics at diagnosis and clinical course of primary extranodal follicular lymphoma (EFL) have not been extensively described. The International Extranodal Lymphoma Study Group (IELSG) conducted an international retrospective survey aimed to describe the clinical features at diagnosis and the outcomes of FL cases with a clinically dominant extranodal component. The dataset included 605 pathologically reviewed cases from 19 different countries, and their outcomes were compared to those of nodal follicular lymphomas. The two most common presentation sites for EFL were the skin (n = 334) and the gastrointestinal tract (n = 72), with 22 cases having primary duodenal localization. These subsets exhibited unique features at diagnosis and significantly different overall survival (OS) patterns. After a median follow-up of 5.5 years, primary cutaneous lymphomas showed a superior outcome [10-year OS: 89% (95% CI, 83%-93%)], while primary gastrointestinal lymphomas had an intermediate outcome [10-year OS: 79% (95% CI, 59%-90%)]. Among the gastrointestinal lymphomas, primary duodenal lymphomas tended toward the best outcome [10-year OS: 95% (95% CI, 69%-99%)]. Other primary extranodal sites had inferior outcomes [10-year OS: 59% (95% CI, 48%-68%)], similar to primary nodal lymphomas [10-year OS: 57% (95% CI, 49%-64%)]. These findings support the identification of specific primary FL localizations as distinct entities with particular clinical and biological characteristics.
Keywords: dospělí; cutaneous follicular lymphoma; Female; Adult; gastrointestinal follicular lymphoma; mladý dospělý; ženské pohlaví; lidé; Lymphoma, Follicular; Aged, 80 and over; následné studie; míra přežití; prognóza; follicular lymphoma international prognostic Index; extranodal follicular lymphoma; retrospektivní studie; Follow-Up Studies; Male; Aged; Young Adult; duodenal follicular lymphoma; Prognosis; Survival Rate; FLIPI; folikulární lymfom; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Humans